PSIKOEDUKASI KEKERASAN DI MASA KANAK-KANAK, NONSUICIDAL SELF-INJURY, DAN FAKTOR RESILIENSI PADA SISWA SMP MARDI YUANA - Ingelina, Budi; Yuditha, Salshabilla; Satiadarma, Monty; Soetikno, Naomi (Jurnal Serina Abdimas, 2024)
Violence against children is a significant issue occurring in Indonesia and globally. Violence towards children is often influenced by cultural and social norms that tolerate violence. The impact of childhood violence includes cognitive, emotional, and social disturbances, as well as an increased risk of maladaptive behaviors such as Non-Suicidal Self-Injury (NSSI) and depression. Unfortunately, during the middle school years, children may be exposed to violence, and may even engage in NSSI as an emotional response to their circumstances. Therefore, resilience is needed in these middle school students. Resilience is a critical factor in overcoming the negative effects of childhood violence, enabling individuals to process traumatic experiences and build meaning in life. In this Community Service activity, psychoeducation was conducted at Mardi Yuana Middle School in Cicurug, Sukabumi, West Java on April 20, 2024. This research is quantitative in nature, employing a one sample pre-test post-test method. The methods used included pre-tests, lectures, Q&A sessions, discussions, and post-tests. The pre-test results showed limited understanding among students about violence, its impacts, NSSI, and resilience. After psychoeducation, there was a significant increase in understanding about the impacts of violence (from 85.5% to 98.6%), knowledge about NSSI (from 4.1% to 36.5%), and resilience (from 70.3% to 100%). These findings indicate the effectiveness of psychoeducation in enhancing students' awareness and understanding of violence, NSSI, and resilience. This activity also revealed that a majority of participants witnessed violence at school (40.5%) and experienced violence in the family (47.3%). These results emphasize the importance of interventions to reduce violence and support the development of resilience in children and adolescents. ABSTRAK Kekerasan terhadap anak merupakan isu signifikan yang terjadi di Indonesia dan secara global. Kekerasan pada anak seringkali dipengaruhi oleh norma budaya dan sosial yang permisif terhadap kekerasan. Dampak kekerasan masa kanak-kanak mencakup gangguan kognitif, emosional, dan sosial, serta meningkatkan risiko perilaku maladaptif seperti Non-Suicidal Self-Injury (NSSI) dan depresi. Sayangnya, masa SMP, anak-anak dapat terpapar pada kekerasan, bahkan dapat melakukan NSSI sebagai respons emosional terhadap situasi yang ada. Oleh karena itu, dibutuhkan adanya resiliensi pada para siswa SMP ini. Resiliensi merupakan faktor penting dalam mengatasi dampak negatif kekerasan masa kanak-kanak, memungkinkan individu mengolah pengalaman traumatis dan membangun makna hidup. Dalam kegiatan Pengabdian Kepada Masyarakat ini, dilakukan psikoedukasi di SMP Mardi Yuana Cicurug, Sukabumi, Jawa Barat pada 20 April 2024. Peneltian ini merupakan penelitian kuantitatif, dengan jenis penelitian one sample pre-test post test method. Metode yang digunakan meliputi pre-test, ceramah, tanya jawab, diskusi, dan post-test. Hasil pre-test menunjukkan pemahaman terbatas siswa tentang kekerasan, dampaknya, NSSI, dan resiliensi. Setelah psikoedukasi, terdapat peningkatan signifikan dalam pemahaman tentang dampak kekerasan (85.5% menjadi 98.6%), pengetahuan NSSI (4.1% menjadi 36.5%), dan resiliensi (70.3% menjadi 100%). Temuan ini menunjukkan efektivitas psikoedukasi dalam meningkatkan kesadaran dan pemahaman siswa tentang kekerasan, NSSI, dan resiliensi. Kegiatan ini juga mengungkap bahwa sebagian besar peserta menyaksikan kekerasan di sekolah (40.5%) dan mengalami kekerasan di keluarga (47.3%). Hasil ini menekankan pentingnya intervensi untuk mengurangi kekerasan dan mendukung perkembangan resiliensi pada anak-anak dan remaja.